Are Apprenticeships Business Cycle Proof? - Samuel Lüthi; Stefan C. Wolter (Institute of Labor Economics (IZA), 2018)
Although there is evidence that apprenticeship training can ease the transition of youth into the labour market and thereby reduce youth unemployment, many policy makers fear that firms will cut their apprenticeship expenditures during economic crises, thus exacerbating the problem of youth unemployment. Using recent panel data of Swiss cantons and dynamic regression models, we examine the relationship between new apprenticeships and the business cycle. The empirical results suggest that economic shocks induce a rather small, pro-cyclical immediate response in the apprenticeship market. However, within a year after the shock, firms compensate for their immediate reaction, with the result that no permanent effect is observable.
Keywords: E24; E32; I21; J18; J44; 330; apprenticeship training; VET; education; business cycle; error correction model